2019
DOI: 10.1016/j.parkreldis.2018.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of self-perceived stigma in Parkinson's disease

Abstract: Objective: The burden of PD extends beyond physical limitations and includes significant psychosocial adjustments as individuals undergo changes to their self-perception and how others perceive them. There is limited quantitative evidence of the factors that contribute to selfperceived stigma, which we addressed in the present study. Methods:In 362 individuals with PD (157 women, 205 men), self-perceived stigma was measured by the four-item stigma subscale of the Parkinson's Disease Questionnaire (PDQ-39). Hie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 31 publications
(33 reference statements)
4
31
0
Order By: Relevance
“…Moreover, depression was strongly related to the score of felt SSCI. This finding was in accord with the work by Salazar et al who recognized that depression was a significant predictor in stigma and depression mediated the relation between stigma and activities of daily living (13). A British study shows that 46% of PD patients stopped working after 5 years of illness, and more than half of them chose to retire early, resulting in economic burden and psychological pressure of patients (22).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, depression was strongly related to the score of felt SSCI. This finding was in accord with the work by Salazar et al who recognized that depression was a significant predictor in stigma and depression mediated the relation between stigma and activities of daily living (13). A British study shows that 46% of PD patients stopped working after 5 years of illness, and more than half of them chose to retire early, resulting in economic burden and psychological pressure of patients (22).…”
Section: Discussionsupporting
confidence: 86%
“…Meanwhile, invisible stigma is the realization of a self with PD, a form of disability, which attested to the mounting isolation (11). Recently, a few studies revealed that difficulties in activities of daily living, younger age, and higher depression scores were the significant predictors of stigma (13,14). However, relative studies are limited in China.…”
Section: Introductionmentioning
confidence: 99%
“…In support of the idea that the spatial attentional bias is modulated by emotional states, we recall that patients with Parkinson's and individuals with post-traumatic stress disorder have pathological values at TAS-20, in fact being alexithymic (Salazar et al, 2019).…”
Section: Discussionsupporting
confidence: 66%
“…Szymura Physical inactivity increases the risk of depression in both HOA and individuals with PD (Gustafsson et al, 2015;Lee et al, 2014), who, in general, have a higher risk of suffering from depression than HOA (Wu et al, 2017). Therefore, the reduction of depressive symptoms in both Disease-related stigma affects quality of life, increases the risk of depression, social isolation, and is common in PD (Hermanns, 2013;Ma et al, 2016;Salazar et al, 2019). Thus, felt (e.g., shame, embarrass-…”
Section: Discussionmentioning
confidence: 99%